Analisis Tata Letak Fasilitas Lsu Farm Melalui Metode Activity Relationship Chart (ARC) Dan Total Closeness Rating (TCR) - Khoirul Aziz Husyairi; A. Ricco Galang Erlangga; Enjelina Damayanti; Maunisa Widya Zalianty; Novia Miftakhul Qisthi; Tina Nur Ainun (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
Efficiency problems in spatial planning at LSU Farm have a significant impact on the effectiveness of the production process. The proximity of raw material storage warehouses to sorting and packaging zones results in congestion that disrupts product flow and quality, as well as triggering backtracking and line crossings that are detrimental to materials management. To overcome this, the Activity Relationship Chart (ARC) method was applied which considers interactions between critical areas such as inbound, sort & repack, outbound, warehouse, employees, cold storage and outdoor offices. ARC's analysis compares the importance of connections between facilities for easier access and consumer convenience, as well as reducing unnecessary movements and improving quality control. The analysis results show that the sort & repack area with the highest Total Closeness Rating (TCR) value (117) is a priority in layout reorganization. Based on these findings, it is recommended that production input warehouses be positioned further away from sorting and packaging areas to maintain product quality and avoid chemical contamination, in line with improving overall operational efficiency.